Kekerabatan Bahasa Lio dan Bahasa Sikka - Radjalewa, Cosmas Reynold; Hendrokumoro, Hendrokumoro; Pita, Yul Fulgensia Rusman (Department of Languages and Literature, Faculty of Cultural Sciences, UGM, 2025)
This article describes and identifies shared innovations, phonemic correspondences, percentage of kinship, type of language classification, and separation time of Lio and Sikka in Flores Island. This study uses a historical-comparative linguistic approach. The data used in this study are 200 basic Swadesh vocabulary in Lio and Sikka obtained through interviews with native speakers of both languages and literature research, particularly studies on Lio and Sikka. Using lexicostatistics and glottochronology techniques, this article shows that Lio and Sikka are related languages as they originated from the same language family. This is proven by 13 shared innovation glosses in Lio and Sikka and the discovery of 101 cognate glosses in Lio and Sikka consisting of 20 identical pairs, 62 phonemically correspondent pairs, 14 one-phoneme-different pairs, and 5 phonetically similar pairs. Based on lexicostatistics and glottochronology computation, the percentage of the relatedness of Lio and Sikka is 51%. These two languages are estimated to have split into distinct languages between 340-600 AD.